Diversity of fruit fly species in agricultural area Chott Zahrez Chergui (Djel-fa): First record of Trupanea amoena (Diptera: Tephritidae) in Algeria - Yahiaoui, Siham Rekia; Sehl, Boudjemaa; Marniche, Faiza; Guerzou, Ahlem (Future Science, 2024)
Fruit flies (Diptera: Tephritidae) are cosmopolitan, species-rich, and yet poorly studied in Algeria, particularly in the agro area of Djelfa. We sampled fruit flies in orchard containing three types of trees apricot, fig and grapes at each site, using the yellow traps. Results show that the orchard differed significantly in species richness, abundance, diversity and evenness. A total of 956 individuals distributed by nine species of Diptera, including four species of fruit flies are collected. The results revealed that most abundant species are Drosophila melanogaster at the apricot fruit site (RA%=28.32%), Zaprionus indianus at fig fruit site (RA%=34.74 %) and Tephritis praecox at the grapes fruit site with (RA%= 51.61 %). The orchard selected a greater number of species and individuals, and higher diversity indices H′=2.40 bits; 2.32 bits and 2.02 bits. Statistically, the result of stepwise multiple regressions revealed a very strong correlation between the number of fruit fly species and the temperatures with (r=93.1%) and (Sig .000**). Thus, fruit flies appear to have rather arrow with the host plant requirements and their phenology was correlated with environmental differences. Our study highlighted for; the first time; the presence of Trupanea amoena in Algeria. This important and substantial preliminary work on this new species in Algeria provides a solid basis for future research and extension of the study in particular for monitoring and control of this dreaded agricultural pest.